THE INFLUENCE OF PERCEPTION AND ATTITUDE TOWARD ZAKAT, INFAQ, AND ALMIGHTY INTEREST IN OVERCOMING POVERTY LEVELS IN INDONESIA (CASE STUDY IN YOGYAKARTA) - Taufik Riza Mahendra; Yuni Sarah; Ghina Fitriani (Universitas Airlangga, 2021)
Zakat, infaq and alms are a solution in overcoming the problems of poverty levels and inequality of welfare in Indonesia, which have become problems that continue to be faced today. In Islam, the law for a person to give zakat is obligatory for those who already have assets that reach the nisab in one year. Zakat aims to distribute assets so that there are no social problems, both poverty levels and socio-economic disparities. Meanwhile, infaq and alms in Islam are voluntary. However, if these three activities are carried out on a large scale, it will affect the economic level of a country. The purpose of this research is to see how much someone cares and how much interest is someone in helping other members of society who are less well off and do not have power in the economy. The method used in this research is quantitative-descriptive with multiple linear regression data processing using SPSS 26 analysis tools. The results of the research conducted show that there is an influence of perceptions and attitudes on the interest in zakat, infaq and alms.